Death before dying : the Sufi poems of Sultan Bahu - Sult̤ān Bāhū, 1630-1691 (University of California Press, 1998)
Death Before Dying offers a window on the Sufi mystical tradition, providing a rare glimpse into the religious lives of rural Muslims during the days of the Mughal Empire. The poetry of Sultan Bahu has inspired Sufis of the Punjab for countless generations, embodying essential characteristics of the mystical tradition, especially in its emphasis on complete and unrestricted devotion to God coupled with skepticism toward the formal, legalistic, and institutionalized elements of organized religion.